Small-to-Medium-Scale Sensory Evaluation of Horticultural Crops—Sensory Testing Methods - Sean Michael Campbell; Charles A. Sims (EDIS)
This new 7-page publication of the Environmental Horticulture Department is fourth in a series designed to assist small-to-medium-sized producers in the sensory evaluation of their horticultural crops, summarizing the discrimination and preference sensory testing methods available, with the guidelines outlined in this publication taken from the 2nd edition of Sensory Evaluation Of Food: Principles And Practices (Lawless and Heymann 2010). Written by Sean Campbell and Charles Sims.